A highly conductive porous graphene electrode prepared via in situ reduction of graphene oxide using Cu nanoparticles for the fabrication of high performance supercapacitors. Issue 67 (24th July 2015) - Zhang, Jizhen; Xu, Yuanhong; Liu, Zhen; Yang, Wenrong; Liu, Jingquan
<x xml:space="preserve">Abstract</x> A new graphene/Cu nanoparticle composite was prepared via the in situ reduction of GO in the presence of Cu nanoparticles which was then utilized as a sacrificing template for the formation of graphene electrodes for supercapacitors.